Task formalization of constructing rational product assembly sequence - Чибіряк, Яна Іванівна; Федотова, Наталія Анатоліївна; Думанчук, Михайло Юрійович (Technology audit and production reserves, 2015)
Analysis of technology of assembly processes has allowed developing mathematical models that reflect the structure of the product and the production system. Ways of reducing the production cycle are defined. On this basis, the rules are designed to rationalize assembly operations. It is proposed a method of constructing a rational product assembly sequence. Its design takes into account the requirements of safety, assembly dimensional chain, simultaneous installation of several based elements on the base, precision of parts manufacturing, allocation of component assembly. A method of solving this problem is characterized in that the assembly for this synthesis process is considered complex and environmental constraints. It provides the necessary quality of the product. Application of the method allows to obtain a sequence of assembly, which is suitable for practical implementation in a given production system and to minimize the duration of the production cycle.